2016
DOI: 10.1007/s10753-016-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142-3p Inhibits Chondrocyte Apoptosis and Inflammation in Osteoarthritis by Targeting HMGB1

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degradation and joint inflammation in which microRNAs are significantly involved. Previous studies have reported that miR-142-3p is a novel mediator of inflammatory signaling pathways, but whether miR-142-3p regulates OA remains unknown. In this study, we aimed to investigate the potential role of miR-142-3p in OA and the underlying molecular mechanism. We showed that miR-142-3p was significantly reduced in the articular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 48%
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 48%
“…This miRNA has been involved in signaling leading to enhanced inflammation. In regard to joint pathology, the expression level of miR-142 was found to be reduced in the cartilage in a mouse model of osteoarthritis [67]. Furthermore, over-expression of miR-451 resulted in inhibition of chondrocyte apoptosis and inflammation in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting specific miRNAs may provide promising strategies for the treatment of OA: For example, miR-142-3p constituted an anti-apoptotic molecule in vitro, and its overexpression impeded OA progression in mice in vivo, indicating that miR-142-3p might be a potential molecular target for OA treatment [275]. Conversely, miR-155, an inhibitor of autophagy, was found to be overexpressed in OA: Developing an anti-sense strategy might contribute in restoring autophagy in chondrocytes [276].…”
Section: Targeting Chondrocyte Apoptosis For Oa Treatmentmentioning
confidence: 99%